Mosquito diversity from the Urutaú Natural Reserve (Misiones, Argentina) - Muttis, Evangelina (2023)
Urutaú Natural Reserve is a protected area in the southwest of Misiones province, Argentina. Regarding the mosquito fauna, 194 species have been recorded for Misiones province so far. It is known that many of them are vectors of pathogens and parasites that cause human and animal diseases. The objective of this work is to understand the mosquito community in order to consider their importance in pathogens and parasites transmission and compare different capturing techniques for mosquito diversity. Larvae, pupae and adults were collected. Comparing the number of species and individuals captured as adult with different methodologies, Net /insect hand aspirator was the most effective methodology capturing diversity of species while CDC light trap captured significantly higher number of individuals. We confirmed the presence of 30 mosquito species belonging to nine genera, of which 12 are suspected of being involved in pathogen transmission. Among them, Sabethes (Sabethes) albiprivus Theobald, the only mosquito from which the Yellow fever virus has been isolated in Argentina. Additionally, we recorded Culex (Culex) lahillei Bachmann & Casal for the first time in Misiones province, and Aedes (Protomacleaya) terrens (Walker) and Culex (Melanoconion) ribeirensis Forattini & Sallum are new citations for Capital Department, Misiones.